The Inhibition Effect of Liqurice (Glycyrrhiza glabra ) on some bacteria: Maysoon Sabah Abbas and Ekram Abbas Abood AL- Samarrae - Abbas, Maysoon Sabah (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to investigate the inhibition role of Liqurice (Glycyrrhiza glabra ) on some bacteriaspp ., Watery and Oily Liqurice extracts prepared to study the inhibition effect on ( Listeria monocytogenus ,Brucella abortus , Brucella meletensis , Escherichia. coli , Pseudomonus aeruginosa , Bacillus anthracisSterne strain , Salmonella typhimurium , Klebsiella pneumoniae , Staphylococcus aureus ) serial platespowered with cultural media Nutrient Agar were inoculated with one of each bacteria studied then filter papersfilled with each type of Liqurice extracts were added and after incubation period then the inhibition Zone weremeasured . the results revealed that inhibition effect of mixed and Oily Liqurice extracts was more effected onL. monocytogenus , S. aureus, P. aeruginosa , B. anthracis Sterne strain , K. pneumoniae . The mixed extracthad no inhibition effect on Br. abortus , Br. meletensis , E. coli , the Oily Liqurice extract had no inhibitioneffect on Br. meletensis , S. typhimurium the watery extract had no inhibition effect on the bacteria in this study